The Varieties of Resource Experience : Natural Resource Export Structures and the Political Economy of Economic Growth - Isham, Jonathan (Published by Oxford University Press on behalf of the World Bank, 2014)
Many oil, mineral, and plantation crop-based economies experienced a substantial deceleration in growth following the commodity boom and bust of the 1970s and early 1980s. This article illustrates how countries dependent on point source natural resources (those extracted from a narrow geographic or economic base, such as oil and minerals) and plantation crops are predisposed to heightened economic and social divisions and weakened institutional capacity. This in turn impedes their ability to respond effectively to shocks, which previous studies have shown to be essential for sustaining rising levels of prosperity. Analysis of data on classifications of export structure, controlling for a wide array of other potential determinants of governance, shows that point source and coffee and cocoa exporting countries do relatively poorly across an array of governance indicators. These governance effects are not associated simply with being a natural resource exporter. Countries with natural resource exports that are diffuse relying primarily on livestock and agricultural produce from small family farms do not show the same strong effects and have had more robust growth recoveries.